Changes in Assessment and Its Influence on Student Learning in Secondary Schools in Brunei Darussalam - Abu Bakar, Norwati; Untong, Roslan; Jait, Awang Karhan (Journal of Social Transformation and Regional Development, 2021)
This study is a phenomenological study that uses a qualitative approach. Seven participants were selected in this study by objective sampling. Data were obtained in triangulation involving various methods of data collection, namely by using in-depth interview methods, non-participant direct classroom observations, and documentary evidence. Findings show that the influence of assessment on learning among them is the mastery of lesson materials, improving academic achievement, and student attitudes. Overall, the findings of the study show that assessment changes have a positive influence on student learning in Islamic Education. It is therefore hoped that the assessment introduced will strengthen its implementation at all levels of schooling.